Bacteriophage infections of microbiota can lead to leaky gut in an experimental rodent model. Issue 1 (December 2016) - Tetz, George; Tetz, Victor
Abstract Increased intestinal permeability and translocation of gut microbiota from the intestinal lumen to the systemic circulation predispose patients to various diseases and may be one of the main triggers thereof. The role of microbiota in increased intestinal permeability is under intensive investigation. Here, we studied alterations in the host and increased intestinal permeability as a direct effect of treatment with a bacteriophage cocktail. After 10 days of challenge, the rats showed weight loss, messy hair, and decreased activity. Additionally, they displayed a significantly elevated lactulose:mannitol ratio and the level of circulating immune complexes. To our knowledge, this study demonstrates for the first time that increased intestinal permeability may be induced by bacteriophages that affect the microbiota.